2019
DOI: 10.1101/643890
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Molecular Inverse Comorbidity between Alzheimer’s disease and Lung Cancer: new insights from Matrix Factorization

Abstract: Matrix Factorization (MF) is an established paradigm for large-scale biological data analysis with tremendous potential in computational biology.We here challenge MF in depicting the molecular bases of epidemiologically described Disease-Disease (DD) relationships. As use case, we focus on the inverse comorbidity association between Alzheimer's disease (AD) and lung cancer (LC), described as a lower than expected probability of developing LC in AD patients. To the day, the molecular mechanisms underlying DD re… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
3
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 61 publications
(62 reference statements)
0
3
0
1
Order By: Relevance
“…Cancer incidence [25], particularly lung cancer [26], seems to be lower in AD and in other central neurodegenerative diseases. Several observations from animal models, transcriptomic meta-analyses, and matrix factorization studies underline the existence of molecular substrates supporting the hypothesis of an inverse comorbidity relationship between AD and lung cancer [27-29].…”
Section: Introductionmentioning
confidence: 99%
“…Cancer incidence [25], particularly lung cancer [26], seems to be lower in AD and in other central neurodegenerative diseases. Several observations from animal models, transcriptomic meta-analyses, and matrix factorization studies underline the existence of molecular substrates supporting the hypothesis of an inverse comorbidity relationship between AD and lung cancer [27-29].…”
Section: Introductionmentioning
confidence: 99%
“…This suggests that a propensity towards one family of diseases may decrease the risk for the other. As an example, AD patients are less prone to develop lung cancer [24][25][26][27], and a history of smoking related cancers has a protective impact against AD [15]. Also for amyotrophic lateral sclerosis (ALS) a decreased frequency of cancer is observed after disease onset [28], although a cancer diagnosis does not affect the occurrence of ALS [29,30].…”
Section: Epidemiological Studies Associate Neurodegeneration and Cancermentioning
confidence: 99%
“…For example, several epidemiologic studies [6][7][8] have demonstrated a risk reduction for Alzheimer's disease after a cancer diagnosis (including lung cancer) [9][10][11]. Moreover, transcriptomic studies [12][13][14] have indicated that the genes upregulated in Alzheimer's disease and downregulated in cancer, as well as the genes downregulated in Alzheimer's disease and upregulated in cancer were signifcantly overlapped. In addition, expression deregulation in opposite directions was observed at the level of pathways in Alzheimer's disease and cancer [15].…”
Section: Introductionmentioning
confidence: 99%